How the Biological/Social Divide Limits Disability and Equality - Martha T. McCluskey (Washington University Journal of Law & Policy, 2010)
If race and gender remain the most valuable currency of identity, Martha McCluskey’s Article intervenes to introduce other emergent categories. Her contribution, How the Biological/Social Divide Limits Disability and Equality, unpacks and criticizes the trajectory along which identity claims are expanding. She uncovers implicit rankings of race, gender, and disability operative in equality jurisprudence, showing how these rankings are reversed under formal and substantive equality models. Next, delving into the struggle for disability justice, she introduces and compares medical and social construction models of disability. Her Article contrasts how law defines disability under workers' compensation rules versus the Americans with Disabilities Act to show that, while these legal regimes implement differing models of disability, neither achieves substantive justice. Criticizing the limits of the social construction move in disability scholarship and law, McCluskey urges that the question "is not which physical differences are socially irrelevant, but which socially interpreted physical differences are relevant to legitimate substantive social functions . . . ." Her Article ends by embracing Martha Fineman's shared vulnerability model as best suited to render substantive justice.
Keywords: People with disabilities; Workers' compensation; Sex discrimination; Race discrimination; Equal rights; United States. Americans with Disabilities Act of 1990; Equal protection; Handicapped discrimination